Cisplatin Loaded Multiwalled Carbon Nanotubes Induce Resistance in Triple Negative Breast Cancer Cells - Madalina Andreea Badea; Mariana Prodana; Anca Dinischiotu; Carmen Crihana; Daniela Ionita; Mihaela Balas (MDPI AG, 2018)
In this paper we developed a method for multiwalled carbon nanotubes (MWCNTs) use as carriers for a drug based on platinum in breast cancer therapy. The method of functionalization involves the carboxyl functionalization of nanotubes and encapsulation of cisplatin (CDDP) into MWCNTs. The biological properties of MWCNTs loaded with CDDP (MWCNT-COOH-CDDP) and of individual components MWCNT-COOH and free CDDP were evaluated on MDA-MB-231 cells. Various concentrations of CDDP (0.316⁻2.52 µg/mL) and MWCNTs (0.5⁻4 µg/mL) were applied on cells for 24 and 48 h. Only at high doses of CDDP (1.26 and 2.52 µg/mL) and MWCNT-COOH-CDDP (2 and 4 µg/mL) cell morphological changes were observed. The cellular viability decreased only with approx. 40% after 48 h of exposure to 2.52 µg/mL CDDP and 4 µg/mL MWCNT-COOH-CDDP despite the high reactive oxygen species (ROS) production induced by MWCNTs starting with 24 h. After 48 h, ROS level dropped as a result of the antioxidant defence activation. We also found a significant decrease of caspase-3 and p53 expression after 48 h, accompanied by a down-regulation of NF-κB in cells exposed to MWCNT-COOH-CDDP system which promotes apoptosis escape and thus failing to overcome the triple negative breast cancer (TNBC) cells resistance.